CHARACTERISTICS OF RUBBER SHEET WITH RAW MATERIAL OF COMPOSITE MODIFICATIONS - LATEX - Marlina, Popy; Adi Prasetya, Hari (Jurnal Dinamika Penelitian Industri, 2017)
Natural starch can be made into modified starch with the desired properties or as needed. Composite of starch and natural rubber for the made of rubber sheets as an alternative to reduce the use of natural rubber in large quantities. The research aimed to study the characteristics of sheets rubber with composite modified starch - latex. The experimental research used non Factorial Completely Randomized Design and each treatments was replicated three times. Single factor of starch and latex modification ratio (Treatment A Starch modification: latex = 1: 1 (500 ml: 500 ml, Treatment B Starch modification:latex = 1:2 (500 ml: 1000 ml and Treatment C Starch modification:latex = 2:1 (1000 ml: 500 ml)). The parameters were plasticity (Po), plasticity resistance index (PRI), mooney viscosity and dirt content. Results showed that the comparison treatment of starch and latex modifications have a influence on the characteristics of sheet rubber meet the quality requirements of Standard Indonesian Rubber (SIR) 20 SNI 06-1903-2000 and standard quality commercial sheets rubber with charactheristics plasticity (Po), plasticity resistance index (PRI), mooney viscosity and dirt content.